Polycystic Ovary Syndrome Current and Emerging Concepts - Pal, Lubna (Springer eBooks, 2014)
Presenting an overview of the current understanding of the pathophysiology of PCOS and a paradigm for the clinical evaluation and management of the disorder, Polycystic Ovary Syndrome is written in an easy to digest, concise format that, with bulleted key points introducing each chapter, is suitable for the trainee and the busy clinician. The breadth and depth of coverage of today's queries and controversies will be of particular interest to the specialist and researcher. An international group of leading experts addresses the varied etiologies of PCOS, comprehensively covering the contemporary treatment approaches and long-term implications of PCOS, a common yet poorly understood disorder. Chapters on treatment will be of particular relevance to the clinician and the trainee as they cover conventional therapies, lifestyle, and diet, as well as address emerging strategies such as the use of statins and surgery in PCOS management.  Spanning the breadth of clinical presentations and morbidities related to the diagnosis of PCOS, Polycystic Ovary Syndrome is an exceptional resource for primary care providers, gynecologists, reproductive endocrinologists, and others involved in the care of these patients, and provides the essential tools to aid clinicians in initiating a timely diagnostic workup and appropriate interventions to address both the immediate and long-term sequelae related to PCOS.